First report of novel mutation (c.790del) on SQSTM1 gene on a family with childhood onset of progressive cerebellar ataxia with vertical gaze palsy. Issue 8 (9th August 2022) - Jalali, Hossein; Khoshaeen, Atefeh; Mahdavi, Mohammad Reza; Mahdavi, Mahan
Abstract: SQSTM1 gene encodes a protein called p62 that acts as an autophagy receptor in the degradation of protein molecules. A homozygous deletion variant that changes the frame shift in the SQSTM1 gene named c.790 Del A .T was detected in case childhood onset and progressive neurodegeneration with ataxia, and gaze palsy.